Judith Deim and Children - unknown:::Creator::::::::::::
Judith Deim with children. Deim painted the only known portrait of Steinbeck at work, writing his first draft of The Sea of Cortez, at her studio in 1941.The Center owns this painting. Later, Steinbeck funded a painting expedition that Deim and (husband) Graham made to central Mexico. Deim, who was born in Saint Louis, Missouri, went on to live in France, Spain, Portugal, Morocco, Senegal, Mexico, Belgium, Crete, and Guatemala. Digital copy only. No hard copy.